Effect of Intellectual Capital and Corporate Social Responsibility on Firm Value Mediated by Financial Performance - Sri Wahyuni; Sri Rahayu; Wirmie Eka Putra (PT. Riset Press International, 2026)
This study aims to analyze the influence of Intellectual Capital (IC) and Corporate Social Responsibility (CSR) on Firm Value with Financial Performance as a mediating variable. The focus on the financial sector is driven by intense competition and the need to enhance firm value through effective IC management and CSR implementation. Moreover, inconsistencies in previous research findings and issues related to CSR fund misuse further strengthen the urgency of this study. The method used is a Systematic Literature Review (SLR) involving 15 articles obtained from Google Scholar. The findings indicate varied results: (1) IC and CSR are expected to positively affect Firm Value, yet some studies report negative or insignificant effects due to poor CSR governance or the market’s limited recognition of IC. (2) Financial Performance has been proven to positively influence Firm Value. (3) Financial Performance can mediate the effect of IC and CSR on Firm Value, although some studies show that the mediation does not occur. In conclusion, effective management of IC and proper implementation of CSR must be able to improve financial performance first to provide a strong and sustainable contribution to Firm Value.